Wind speed modeling over complex terrain with the artificial neural network in the measure-correlate-predict technique: A case study of Malaysia - Kim Hwang Y.; Zamri Ibrahim M.; Ismail M.; Najah Ahmed A.; Albani A. (SAGE Publications Inc., 2023)
Complex networks; Forecasting; Genetic algorithms; Neural networks; Wind; Wind power; Case-studies; Complex terrains; Malaysia; Malaysians; MCP; Measure-correlate-predict; Model inputs; Spatial modelling; Wind maps; Wind speed models; Surface roughness; alternative energy; artificial neural network; genetic algorithm; renewable resource; roughness; wind power; Malaysia